PERKEMBANGAN PENELITIAN AKUNTANSI PEMERINTAH PADA DUA JURNAL NASIONAL TERAKREDITASI - Zayyan Velda Send; Puji Wibowo (Jurnal Akuntansi dan Keuangan, 2021)
The adoption of the accrual basis is a milestone in the reform of government financial reporting. State financial management policies in the new government era also provided new insights for the development of government accounting research. This study aims to provide an overview of the development of government accounting research in two reputable national journals indexed by SINTA 2 during the 2015-2019 period. Article observations are carried out using the chartered fields method. The results of a study of 43 articles show that accountability and spending are the most popular topics to be discussed Mixed research methods are still very limited to use in these government accounting studies. This study contributes to the direction of government accounting research in the future by providing signals of several interesting research areas to be explored further.